CORRECTION WITH VITAMINS AND MINERALS IN CHILDREN: PRO AND CONTRA? - I.М. Kosenko ("Paediatrician" Publishers LLC, 2010)
Author examines a role of micronutrients in development and health state of children. Main causes of vitamins and mineral deficiency are presented. It was shown that prophylaxis of micronutrients insufficiency with complexes of vitamins and minerals must be obligatory. The article presents main criteria of choice of such drugs.Key words: children, vitamins, minerals, hypovitaminosis, complexes of vitamins and minerals.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):132-137)